Stop animal cruelty for exotic lifestyle awareness campaign in Malaysia / Nur Aishah Kamal Rizaman - Kamal Rizaman, Nur Aishah (2022)
Animal are our friends, neighbors and have an interest in the environment. Animals need support from us to survive from irresponsible parties. Animals need humans to show events that take place around without the knowledge of society by confronting and taking actions such as not buying goods from animal skins. Reptiles are the most widely used animals in the field of fashion on the world stage for example crocodiles and snakes. They use these animals to produce various types of products and have received a warm response from consumers especially those who are interested in fashion. Tiger, leopard, ostrich also used to produce products from its skin such as shirts, handbags and more. Society does not know that the response from buying goods from animal skins has caused animals to become extinct because of their greedy attitude. The public does not know the disadvantages when using products from the skins of these animals as they are not exposed to this. They need to know how the process to produce a product using animal skins such as catching animals, the process in peeling animal skins and the process of producing goods after finishing washing animal skins. The matter is not disclosed to the public as it is a matter of privacy from the agency that manages these animals. This study aims conducted is intended for society to know more about brands name that use animal skins and research aims for society know the cruelty behind our products using animal skin.